UNCERTAINTY DEFINITION IN STRUCTURAL SYSTEMS WITH ELASTO-PLASTIC MATERIALS UNDER THE BENDING MOMENT EFFECT BY USING INTERVAL ANALYSIS - Erdolen, Ayse (TAYLOR & FRANCIS INC, 2013)
In this study, material and/or geometrical uncertainties were embodied into calculations by using interval analysis in symmetrical structural systems that display elasto-plastic material behavior when exposed to the pure bending moment effect, and the moment bearing capacities of the systems under these uncertainties were determined. The parameters used in the formulas, which are considered to be affected by the uncertainties, are defined under two sections: certain and uncertain. The uncertain section is expressed with interval numbers and then added to the actual value as a multiplying factor. By using interval analysis in the applications that require maximum sensitivity, the content of correct result is guaranteed, by enabling the use of a solution interval that includes the actual value, without considering the source of the uncertainty.
Keywords: Elasto-plastic behavior; Interval analysis; Uncertainty; OPTIMIZATION; STIFFNESS; Mechanics